Current Evidence-based Indications for Modern Noncemented Total Knee Arthroplasty. Issue 20 (15th October 2020) - Christensen, David D.; Klement, Mitchell R.; Moschetti, Wayne E.; Fillingham, Yale A.
Abstract : Total knee arthroplasty (TKA) is one of the most common procedures performed in orthopaedic surgery. Traditionally, most TKAs have been performed by cementing the implant to the bone with polymethyl methacrylate to provide fixation. Noncemented implants that rely on boney ingrowth for fixation are increasingly appealing to surgeons, given success in total hip arthroplasty and the desire for long-term stability of implants in younger patients. Despite high failure rates with early designs, several series of recent designs have demonstrated improved survivorship, although this has not been confirmed in larger registry studies. Modern screwless designs with improved porous coating are thought to contribute to better ingrowth and have been designed to address previous implant pitfalls. Surgeons must be aware of the potential advantages and limitations of noncemented TKA.